2012
DOI: 10.1111/j.1574-6968.2012.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Broad diversity of conjugative plasmids in integron-carrying bacteria from wastewater environments

Abstract: In this study we assessed the occurrence, diversity and conjugative potential of plasmids in integron‐carrying Aeromonas and Enterobacteriaceae from wastewaters. Sixty‐six strains were included as donors in mating assays using rifampicin‐resistant Escherichia coli and Pseudomonas putida recipient strains. The diversity of plasmids from donors and transconjugants (resistant to tetracycline or streptomycin) was evaluated by restriction analysis and replicon typing targeting 19 incompatibility groups. Restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…It has been shown that the persistence of antibiotics in the environment at sub-therapeutic concentrations contributes to the acquisition of antibiotic resistance genes between different strains, mediated by integrons, as a result of the activation of bacterial SOS responses (Baharoglu et al, 2010; Andersson and Hughes, 2011). In addition, integrons are often associated with conjugative plasmids which contribute to their mobilization and wide dissemination (Moura et al, 2012a). The spread of such determinants can constitute serious environmental risks, compromising both ecosystem and human health.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the persistence of antibiotics in the environment at sub-therapeutic concentrations contributes to the acquisition of antibiotic resistance genes between different strains, mediated by integrons, as a result of the activation of bacterial SOS responses (Baharoglu et al, 2010; Andersson and Hughes, 2011). In addition, integrons are often associated with conjugative plasmids which contribute to their mobilization and wide dissemination (Moura et al, 2012a). The spread of such determinants can constitute serious environmental risks, compromising both ecosystem and human health.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the potential clinical consequences of increasing antibiotic resistance of Aeromonas, their ubiquitous nature may make them a reservoir and ecological vehicle for spreading anti- biotic resistance to other bacteria, including E. coli (35). Antibiotic resistance genes among Aeromonas organisms have been associated with integron-associated R plasmids, and tetracycline resistance, in particular, has been associated with an array of different plasmids within A. hydrophila isolates (36).…”
Section: Fig 2 Prevalences Ofmentioning
confidence: 99%
“…Consequently, in such environments, lateral gene transfer is promoted and there are opportunities for complex interactions between various mobile elements. These interactions can generate ever more complex mosaic molecules that carry a growing armory of genes encoding resistance to diverse selective agents (229)(230)(231)(232).…”
Section: Selection In Natural Environmentsmentioning
confidence: 99%